Hubungan Kegiatan Ekstrakurikuler Pendidikan Kepramukaan dengan Kemandirian Siswa Kelas IV dan Kelas V Sekolah Dasar Negeri 5 Kota Bengkulu - Mike Wahyu Fadma; Lukman Lukman; Resnani Resnani (Universitas Bengkulu, 2019)
This study aims to determine the relationship of extracurricular activities scouting education (X) with the independence of students (Y) class IV and class V As Basic State 5 Bengkulu City. This type of research is quantitative research. The population of this study amounted to 286 students. The sample in this research is 72 students with random sampling sampling technique. Data collection techniques used questionnaires. The research instrument was tested using validity and reliability. While prerequisite analysis test by using normality test and homogeneity test. Data analysis technique is done by using